Binary Opposition in Fast as The Wind Novel by Nat Gould - Aritonang, Bangun Rizky Hanif (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2022)
The purpose of this article is to reveal the binary opposition of Hector Woodridge, one of the characters in Nat Gould's novel Fast as the Wind. This article applies the qualitative method and objective approach. The data in this article were quotations such as words, texts, or sentences that were obtained from Fast as the Wind. This article will also focus on analyzing the character using Derrida's deconstruction theory. This article analyzed the character Hector Woodridge via binary opposition that provides a different view from the story. The findings show three opposite characteristics of Hector Woodridge. The previously fixed thoughts of Hector Woodridge are vengeful, sane, and grateful. After the previous view was deconstructed, the different views are forgiving, mad, and ungrateful. This article tried to signify the different views of Hector Woodridge through binary opposition.